Efforts to Improve the Professionalism of Lecturers' Teaching Through Monitoring and Evaluation of Learning in the Islamic Religious Education Study Program at Idia Prenduan - Ahmadi Ahmadi; Wintang Irawan (Al-Alim: Jurnal Pendidikan Agama Islam, 2026)
This study examines the effectiveness of the monitoring and evaluation (monev) system in improving lecturer professionalism in the Islamic Religious Education (PAI) Study Program at IDIA Prenduan. Using a qualitative approach and case study method, this study analyzed data from in-depth interviews, participant observation, and document review with four key informants. The research findings indicate that the SIMASTER-based monev system successfully increased lecturer compliance with the RPS by 22% (from 65% in 2020 to 87% in 2023), while encouraging 45% of lecturers to adopt active learning methods. However, the implementation of this system faced obstacles in the form of technological resistance from 23% of senior lecturers and negative perceptions of student evaluations (30% of respondents). The uniqueness of this study lies in the integration of Islamic boarding school values ​​(al-muhasabah and tazkiyatun nafs) which were proven to be effective in increasing lecturer acceptance of the evaluation process (85% of respondents). This study recommends the development of an integrated monitoring and evaluation model that combines a technocratic approach with the distinctive values ​​of Islamic boarding schools, intensive training for senior lecturers, and the refinement of evaluation instruments based on 360-degree feedback. These findings provide an important contribution to the development of a quality assurance system in religious higher education institutions with a distinctive cultural approach.